Антология выдающихся достижений в науке и технике. Часть 46: Термоядерная энергетика. Термоядерные реакторы и электростанции: ретроспектива исследований управляемого термоядерного синтеза, их современное состояние и будущее - Баранов, Михаил Иванович (Національний технічний університет "Харківський політехнічний інститут", 2018)
Приведен научно-технический обзор о ретроспективе исследований в ведущих странах мира управляемого термоядерного синтеза (УТС) легких ядер, современном состоянии разработок и возможных перспективах мирового развития наукоемкой техники в области термоядерной энергетики. Приведены ядерно-физические основы процесса протекания УТС в смеси легких ядер. Представлены данные о результатах начального и современного этапов исследований в области УТС. Описаны основные конструкции и технические характеристики термоядерных реакторов (ТЯР), использующих магнитное и инерционное удержание горячей плазмы. Проанализирован мировой прогресс в области разработки, создания и исследования экспериментальных ТЯР, базирующихся на системах удержания горячей плазмы в тороидальных магнитных "ловушках" (установки-токамаки и стеллараторы) и инерционных системах лазерно-импульсной технологии микровзрывов мишеней-капсул термоядерного топлива. Приведены данные об основных видах термоядерного топлива, которое может применяться в рабочих циклах ТЯР, и безопасности ТЯР. Указаны основные проблемы в области УТС для экспериментальных ТЯР и создания в будущем термоядерных электрических станций (ТЯЭС). Отмечена важная роль ТЯЭС и термоядерной энергетики в обеспечении человечества в долгосрочной перспективе электроэнергией.

Purpose. Preparation of brief scientific and technical review about the retrospective view of investigations, state-of-the art, problems and possible prospects of development in the world of thermonuclear power engineering. Methodology. Known scientific methods of collection, analysis and analytical treatment of the opened scientific and technical information of world level in area of the controlled thermonuclear synthesis (CTS) and thermonuclear power engineering, resulted in scientific monographs, journals and internet reports. Results. A brief analytical scientific and technical review is resulted about the retrospective view of researches, modern state, basic achievements, existent problems and possible prospects of development of thermonuclear power engineering in the leading countries of the world. Nuclear physical bases of process of flowing of CTS are resulted in mixture of light nuclei. Information is presented about the results of the initial and modern stages of world researches in area of CTS. Basic constructions and technical descriptions of thermonuclear reactors (TNR), utilizing the magnetic and inertia withholding of hot plasma are described. World progress is analyzed in area of development, creation and research of experimental TNR, being based on the systems of withholding of hot plasma in toroidal magnetic "traps" (options: tokamaks and stellarators) and inertia systems of laser-impulse technology of microscopic explosions of targets-capsules of thermonuclearfuel. Information is resulted about the basic types of thermonuclear fuel, which can be used in the duty cycles of TNR, and safety of TNR. The basic systems and devices of the largest in the world of experimental TNR-tokamak of ITER type (with a reference cost of EUR 15 billion and term of putting into an experimental operation in 2025), erected now within the framework of international project in France are described. Basic problems are indicated in area of CTS in experimental TNR and creations in the future of the thermonuclear power plants (TNPP). The important role of TNPP and thermonuclear power engineering is marked on the whole in providing of humanity in a long-term prospect electric energy. Originality. Certain systematization of the scientific and technical materials touching the problem of CTS of light nuclei and practical application in the peaceful aims of thermonuclear energy known from the sources opened in outer informative space is executed. It is shown on the basis of approach of the systems, that, in spite of row of existent technical problems in area of creation of industrial TNR and practical commercial capture thermonuclear energy, thermonuclear power engineering has an important value for providing in remote future electric energy of all of humanity. Practical value. Scientific popularization and deepening for the students of technical universities, engineering, technical and scientific workers, working in the power sectorof economy, scientific and technical knowledge in area of CTS and thermonuclear power engineering, extending their scientific range of interests and further development of scientific and technical progress in society.
An anthology of the distinguished achievements in science and technique. Part 46: Thermonuclear power engineering. Thermonuclear reactors and power plants: retrospective view of investigations of the controlled thermonuclear synthesis, their state-of-the-art and future
Keywords: токамак; стелларатор; лазерно-импульсный реактор; безопасность; термоядерная электрическая станция будущего; мировая термоядерная энергетика; tokamak; stellarator; laser-impulse reactor; safety; thermonuclear power plant of the future; world thermonuclear power engineering